Reaching measures and feedback effects in auditory peripersonal space - Hug, Mercedes Ximena (2019)
We analyse the effects of exploration feedback on reaching measures of perceived auditory peripersonal space (APS) boundary and the auditory distance perception (ADP) of sound sources located within it. We conducted an experiment in which the participants had to estimate if a sound source was (or not) reachable and to estimate its distance (40 to 150 cm in 5-cm steps) by reaching to a small loudspeaker. The stimulus consisted of a train of three bursts of Gaussian broadband noise. Participants were randomly assigned to two groups: Experimental (EG) and Control (CG). There were three phases in the following order: Pretest–Test–Posttest. For all phases, the listeners performed the same task except for the EG-Test phase where the participants reach in order to touch the sound source. We applied models to characterise the participants’ responses and provide evidence that feedback significantly reduces the response bias of both the perceived boundary of the APS and the ADP of sound sources located within reach. In the CG, the repetition of the task did not affect APS and ADP accuracy, but it improved the performance consistency: the reachable uncertainty zone in APS was reduced and there was a tendency to decrease variability in ADP.